Controllable p‐Type Doping of 2D WSe2 via Vanadium Substitution. (23rd July 2021) - Kozhakhmetov, Azimkhan; Stolz, Samuel; Tan, Anne Marie Z.; Pendurthi, Rahul; Bachu, Saiphaneendra; Turker, Furkan; Alem, Nasim; Kachian, Jessica; Das, Saptarshi; Hennig, Richard G.; Gröning, Oliver; Schuler, Bruno; et al.
Abstract: Scalable substitutional doping of 2D transition metal dichalcogenides is a prerequisite to developing next‐generation logic and memory devices based on 2D materials. To date, doping efforts are still nascent. Here, scalable growth and vanadium (V) doping of 2D WSe2 at front‐end‐of‐line and back‐end‐of‐line compatible temperatures of 800 and 400 °C, respectively, is reported. A combination of experimental and theoretical studies confirm that vanadium atoms substitutionally replace tungsten in WSe2, which results in p ‐type doping via the introduction of discrete defect levels that lie close to the valence band maxima. The p ‐type nature of the V dopants is further verified by constructed field‐effect transistors, where hole conduction becomes dominant with increasing vanadium concentration. Hence, this study presents a method to precisely control the density of intentionally introduced impurities, which is indispensable in the production of electronic‐grade wafer‐scale extrinsic 2D semiconductors. Abstract : Scalable substitutional vanadium doping of 2D WSe2 is achieved via MOCVD at FEOL and BEOL compatible temperatures. Detailed experimental and the first‐principles calculations demonstrate that vanadium dopants introduce discrete acceptor levels that lie within the valance band. Transport measurements further confirm the p ‐type nature of the vanadium dopants where hole conduction is dominant with increasing the dopant concentration.